Religious Moderation Education Model in Islamic Boarding Schools Based on the Teachings and Strategies of the Walisongo's Da'wah - Ihsan, Ihsan; Khafidzin, Zaenal; Zuhri, Achmad (Program Studi Pendidikan Agama Islam, 2024)
This article aims to analyze the model of religious moderation education in Islamic boarding schools, focusing on the implementation of Walisongo's da'wah teachings and strategies. The development of Walisongo's da'wah teachings and strategies is essential for reinforcing religious moderation in Islamic boarding schools, thereby serving as a model for religious moderation education. This study falls under the category of qualitative descriptive research. The phenomenological approach was employed to investigate the implementation of Walisongo's da'wah teachings and strategies in religious moderation education within Islamic boarding schools thoroughly and comprehensively. This study was carried out in Central Java Province, utilizing purposive sampling to select participants from Al-Hidayat Lasem Islamic Boarding School, Qudsiyyah Kudus Islamic Boarding School, Futuhiyyah Demak Islamic Boarding School, Annawawi Purworejo Islamic Boarding School, and Al-Hikmah Benda Sirampog Brebes Islamic Boarding School. The research data were collected through documentation, observation, and interviews, followed by qualitative descriptive analysis. The study's findings indicate that the teachings and strategies of Walisongo's da'wah, as adopted by Islamic boarding schools in Central Java, encompass the preservation of local wisdom, opposition to fanaticism, promotion of economic independence, nationalism, broad insight, and community protection. The Islamic boarding school curriculum includes teachings, instructional materials, examples set by Kiai, and the prevailing culture, which collectively fosters student behaviors characterized by tolerance, respect for ulama, historical awareness, trustworthiness, knowledge development, commitment to state principles, and open-mindedness.